2015
DOI: 10.1016/j.wocn.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in phonetic cue use in production and perception of a non-native sound contrast

Abstract: The current work examines native Korean speakers’ perception and production of stop contrasts in their native language (L1, Korean) and second language (L2, English), focusing on three acoustic dimensions that are all used, albeit to different extents, in both languages: voice onset time (VOT), f0 at vowel onset, and closure duration. Participants used all three cues to distinguish the L1 Korean three-way stop distinction in both production and perception. Speakers’ productions of the L2 English contrasts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
131
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(142 citation statements)
references
References 60 publications
(123 reference statements)
8
131
2
1
Order By: Relevance
“…In previous work (Schertz et al, 2015), we found substantial variability in native Korean listeners’ cue weighting strategies in distinguishing their L2 English stop contrast: while some Korean listeners used primarily VOT to distinguish the contrast in a forced-choice task, like native English listeners do, most either used primarily f0, or made use of both dimensions (requiring both long VOT and high f0 to categorize stimuli as voiceless /p/). This tendency to rely on f0 likely stems from the fact that the three-way stop contrast in Korean relies heavily on both VOT and f0 (e.g.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…In previous work (Schertz et al, 2015), we found substantial variability in native Korean listeners’ cue weighting strategies in distinguishing their L2 English stop contrast: while some Korean listeners used primarily VOT to distinguish the contrast in a forced-choice task, like native English listeners do, most either used primarily f0, or made use of both dimensions (requiring both long VOT and high f0 to categorize stimuli as voiceless /p/). This tendency to rely on f0 likely stems from the fact that the three-way stop contrast in Korean relies heavily on both VOT and f0 (e.g.…”
mentioning
confidence: 76%
“…Cho et al, 2002; Lee and Jongman, 2012). Interestingly, Korean speakers vary both VOT and f0 to an equal extent when distinguishing their L2 English stop contrast in production (Schertz et al, 2015), but this cue use is not necessarily reflected in their perception . The factors underlying these differences in phonetic structure are not yet known; however, recent work by Kong and Yoon (2013) suggests that listeners’ level of English proficiency plays a role, with higher-proficiency speakers using f0 less (i.e.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to changes in the dimensional relationship between two properties of speech leads to changes in perception (dimension-based statistical learning) but only if the manipulation did not violate typical learned long-term relationship regularity between the two dimensions (e. g., Idemaru & Holt, 2011). Recent examples show that changes in perception are sensitive to specific languages (Schertz, 2014), individual biases (Schertz, Lotto & Warner, 2015), and to linguistic experience (Cooper, 2016). What is the basis for these differences?…”
Section: Generalizationmentioning
confidence: 99%